Enhancing the performance of defected ground structure type near‐field radiofrequency WPT system by coupled‐line impedance matching. Issue 12 (29th July 2020) - Verma, Shalin; Rano, Dinesh; Hashmi, Mohammad
Abstract : This study reports, for the first time, the use of coupled‐line‐based impedance matching in wireless power transfer (WPT) system. The transmitter and receiver of the WPT system are realised by microstrip feed line and symmetric coupled line at the top plane. The ground plane is realised with triangular‐shaped defect along with the excitation slot mounted by an external capacitor. The defect in the ground plane and the external capacitor regulate the resonant frequency and also enable miniaturisation of the WPT system. The design is augmented with a systematic analytical approach for impedance matching and a simplified design procedure for the WPT system. A novel equivalent circuit model consisting of parallel LC network and coupled lines is also developed for the evaluation of the proposed WPT system design technique. A prototype of the system operating at 300 MHz developed on Rogers RO4350B substrate achieves a peak efficiency of 80% at a transmission distance of 17 mm. An excellent agreement between the measured and the electromagnetic simulated results is a testament of the robustness of the proposed design technique. Furthermore, evaluation of the commonly used WPT‐related figure of merit shows significant enhancement when compared to the existing state of the art.